AN OVERVIEW OF THE ACHIEVEMENT OF THE IMMUNIZATION PROGRAM IN THE WORKING AREA OF PUSKESMAS PASIE RAYA - Nurdin, Ambia; Yanti, Rahma (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2023)
According to the World Health Organization (WHO), around 1.5 million children die each year from immunization-preventable diseases. In 2018 there were approximately 20 million children who did not get complete immunization and there were even children who did not get immunized at all. This study aims to determine the description of the implementation system of the complete basic immunization program for infants in Pasie Raya sub-district, 2021. This type of research uses quantitative research using a descriptive approach. Sampling using the total sampling method, namely 41 immunization section employees at each puskesmas using a questionnaire. Indicators such as planning are carried out routinely, immunization implementation has also been carried out according to schedule, preparation by officers has also gone well, coordination between sectors has also gone well, and the evaluation carried out has also run smoothly. Output indicators covering complete basic immunization coverage still have several puskesmas that have not reached the complete basic immunization target. It is expected that the local government to provide good distribution of funds and strive to increase the coverage of complete basic immunization.